Portrait of a Sakinah Mawaddah Warahmah Family in the Community of Lenggerong Village, Bantarbolang District, Pemalang Regency - Fakhrunnisa Rosada; Fitri Kurniawati (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Purpose – Creating a sakinah mawaddah warahmah family is a goal for every married couple. These efforts are certainly faced with various challenges and obstacles. This is experienced by some people in Lenggerong Village, Bantarbolang District, Pemalang Regency. This research aims to see how the portrait of a sakinah mawaddah warahmah family in the community of Lenggerong Village, Bantarbolang District, Pemalang Regency. Methods – This research uses qualitative research with a descriptive approach technique. The subjects and data sources of this research came from Mrs Sitih, Mrs Istiana and Mrs Eka Jayanti. The data collection techniques were interviews and observations. Findings – The results showed that the portrait of a Sakinah, Mawaddah, warahmah family is a calm family condition, mutual understanding, no turmoil, serene, happy and harmonious. The husband fulfils the obligation of physical and mental nafkah and provides love and affection to the wife. Meanwhile, the wife's obligations towards the husband or the husband's rights over the wife are, among others: Obeying the husband, taking care of yourself when the husband is not around, maintaining self-respect and protecting the husband's property. Research implications/limitations – Based on the results of the study, the researcher recommends that the authorities conduct socialization on the formation of a sakinah family, especially for married couples who are in a long-distance relationship in Lenggerong Village. Originality/value – The existence of this research is expected to be a praxis reference for the community in an effort to form a sakinah mawaddah warahmah family. The empirical experiences of the informants in this study are expected to inspire married couples in other communities to form a sakinah family.